1992
DOI: 10.1530/jrf.0.0940057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of implanting bull calves with testosterone propionate, dihydrotestosterone propionate or oestradiol-17  prepubertally on the pituitary-testicular axis and on postpubertal social and sexual behaviour

Abstract: Twelve non-implanted crossbred bull calves served as controls and 30 crossbred bull calves (10/treatment) were implanted for 82 days, beginning at 34 days of age, to determine the influence of testosterone propionate (TP), dihydrotestosterone propionate (DHTP) and oestradiol-17 beta (E2) on prepubertal and pubertal pituitary-testicular function and on postpubertal social and sexual behaviour. Compared with control bulls, concentrations of serum luteinizing hormone (LH), follicle-stimulating hormone (FSH) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Regardless of sire breed, bulls reached puberty when scrotal circumference reached approximately 28 cm, and PTV reached approximately 300 cm 3 . We have shown previously that Zebu × Bos taurus bulls and bulls of Bos taurus beef breeds reach puberty at 28 cm scrotal circumference (Lunstra et al, 1978(Lunstra et al, , 1988(Lunstra et al, , 1993Godfrey et al, 1992). Consistent with the present results, other researchers have reported that Brahman-, Romosinuano-, Nellore-, Senepol-, and Tuli-sired bulls reach puberty at 27 to 31 cm scrotal circumference (Chase et al, 1997(Chase et al, , 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Regardless of sire breed, bulls reached puberty when scrotal circumference reached approximately 28 cm, and PTV reached approximately 300 cm 3 . We have shown previously that Zebu × Bos taurus bulls and bulls of Bos taurus beef breeds reach puberty at 28 cm scrotal circumference (Lunstra et al, 1978(Lunstra et al, , 1988(Lunstra et al, , 1993Godfrey et al, 1992). Consistent with the present results, other researchers have reported that Brahman-, Romosinuano-, Nellore-, Senepol-, and Tuli-sired bulls reach puberty at 27 to 31 cm scrotal circumference (Chase et al, 1997(Chase et al, , 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have shown that bulls exhibit an increase in level of sexual behavior over time also (Godfrey and Lunstra, 1989;Godfrey et al, 1992). Price et al (1991a) have shown that a brief exposure of young, virgin rams to estrous ewes can increase their level of sexual behavior to a level similar to that of experienced rams.…”
Section: Discussionmentioning
confidence: 98%
“…Testosterone and dihydrotestosterone suppress serum concentrations of LH and FSH in bull calves between 4 and 20 weeks of age (Kennedy et al. 1985; Godfrey et al. 1992).…”
Section: Regulation Of Gonadotropin Secretion During Developmentmentioning
confidence: 99%